2015
DOI: 10.1177/1059840515588956
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of the “Sedentary Lifestyle” Nursing Diagnosis in Secondary School Students

Abstract: This study clinically validated the nursing diagnosis of "sedentary lifestyle" (SL) among 564 Brazilian adolescents. Measures of diagnostic accuracy were calculated for defining characteristics, and Mantel-Haenszel analysis was used to identify related factors. The measures of diagnostic accuracy showed that the following defining characteristics were statistically significant: "average daily physical activity less than recommended for gender and age," "preference for activity low in physical activity," "nonen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 44 publications
1
11
0
2
Order By: Relevance
“…The most frequently identified RF in our study were Insufficient motivation for physical activity and Insufficient resources for physical activity , which are in agreement with WHO data regarding the reasons why people do not practice physical activity, that is, fear of violence and crime in external areas; high traffic density; low air quality, pollution; lack of parks, sidewalks and facilities for sports and leisure (WHO, 2018). Another study that corroborates with some of the RFs identified was performed with students, which identified that insufficient motivation, insufficient resources, and the report of pain were the reasons for lack of physical inactivity (Oliveira et al., ).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The most frequently identified RF in our study were Insufficient motivation for physical activity and Insufficient resources for physical activity , which are in agreement with WHO data regarding the reasons why people do not practice physical activity, that is, fear of violence and crime in external areas; high traffic density; low air quality, pollution; lack of parks, sidewalks and facilities for sports and leisure (WHO, 2018). Another study that corroborates with some of the RFs identified was performed with students, which identified that insufficient motivation, insufficient resources, and the report of pain were the reasons for lack of physical inactivity (Oliveira et al., ).…”
Section: Discussionmentioning
confidence: 63%
“…Studies evaluating the frequency of Sedentary lifestyle in different populations found that it ranged from 55.8% in patients with hypertension (Martins et al., , ) and 48.6% in schoolchildren (Oliveira et al., ). It should be emphasized that prevalence found in our study is similar to that found in patients with ACS by Brunori et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the public health problems of the 21st century, physical inactivity is relevant due to the relevant association with the development of chronic non--communicable diseases (4) . The prevalence of sedentary lifestyle in this study was 68.3%.…”
Section: Discussionmentioning
confidence: 99%
“…The survey of associated factors makes it possible to plan promotion and incentive measures for physical activity practices, and can therefore be a vital element for the prevention of diseases and chronic non-communicable diseases (4) . It is indicated that the earlier this behavior is identified and modified, the greater the possibility of avoiding the sequela of this habit, as well established in the literature (5) .…”
Section: Introductionmentioning
confidence: 99%